2016
DOI: 10.1242/jcs.197533
|View full text |Cite
|
Sign up to set email alerts
|

An unconventional interaction between Dis1/TOG and Mal3/EB1 in fission yeast promotes the fidelity of chromosome segregation

Abstract: Dynamic microtubule plus-ends interact with various intracellular target regions such as the cell cortex and the kinetochore. Two conserved families of microtubule plus-end-tracking proteins, the XMAP215, ch-TOG or CKAP5 family and the end-binding 1 (EB1, also known as MAPRE1) family, play pivotal roles in regulating microtubule dynamics. Here, we study the functional interplay between fission yeast Dis1, a member of the XMAP215/TOG family, and Mal3, an EB1 protein. Using an in vitro microscopy assay, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 91 publications
(158 reference statements)
7
68
1
Order By: Relevance
“…Our previous results indicated that Ndc80 directly or indirectly interacts with the MAP Dis1/chTOG [23] that tracks the plus end of dynamic MTs and possesses a MT polymerase activity as other members of this family [32]. Intriguingly, Dis1 forms a stable complex with the autonomous MT plus-end tracking protein Mal3/EB1, thereby regulating mitotic progression [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous results indicated that Ndc80 directly or indirectly interacts with the MAP Dis1/chTOG [23] that tracks the plus end of dynamic MTs and possesses a MT polymerase activity as other members of this family [32]. Intriguingly, Dis1 forms a stable complex with the autonomous MT plus-end tracking protein Mal3/EB1, thereby regulating mitotic progression [32].…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Dis1 forms a stable complex with the autonomous MT plus-end tracking protein Mal3/EB1, thereby regulating mitotic progression [32]. In addition, it was reported that budding yeast and human orthologues of Dis1, Stu2 and chTOG are capable of directly interacting with the Ndc80 complex [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XMAP215 ortholog in Xenopus and yeast, XMAP215/Dis1/ Stu2 interacts with the MT plus-end tracking protein EB1 (Kronja, Kruljac-Letunic, Caudron-Herger, Bieling, & Karsenti, 2009;Matsuo et al, 2016;Wolyniak et al, 2006) to regulate MT dynamics at the kMT interface (Figures 1e1,e2,g1,g2 and 2b,c). An in vitro study using the purified Ndc80 complex from fission yeast showed that the complex interacted with EB1 to track the growing MT plus-ends, but no detectable binding was observed between the complex and Dis1 (Matsuo, Maurer, Surrey, & Toda, 2017).…”
Section: Xmap215 Family Proteins Generally Function As Mt Polymerases Atmentioning
confidence: 99%
“…TIRF microscopy has shown that the budding yeast Stu2 binds preferentially to MT plus‐ends in vitro and that the fission yeast Dis1 weakly associates with the MT lattice and accumulates specifically at the growing MT plus‐ends (Figures e2 and b,c). In contrast, human chTOG accumulates at both the growing and shrinking MT plus‐ends, and it is thought that MT polymerase activity promotes MT assembly at both growing and shrinking (also called rescue) MT tips (Figures d2 and a (Matsuo et al, ; Podolski et al, ; Roostalu, Cade, & Surrey, ; van Breugel, Drechsel, & Hyman, ). Budding yeast Stu2 and Xenopus XMAP215 have also been reported as MT‐destabilizing factors at the plus‐ends, possibly by inducing catastrophe (Shirasu‐Hiza, Coughlin, & Mitchison, ; van Breugel et al, ).…”
Section: Introductionmentioning
confidence: 99%